Simulation de la mise en forme d’un renfort déséquilibré - Soulat, Damien; Daniel, Jean-Luc; Boisse, Philippe (European Journal of Computational Mechanics, 2004)
The simulation of forming of a very unbalanced woven reinforcement is described and compared with the experimental tests. Simulation is carried out thanks to the development of finite elements specific to fabrics based on the only deformation energy in tension. These elements implemented in explicit dynamics lead to a very simple form of the interior efforts. The results of simulation correctly translate the shape very unbalanced noted in experiments and which had with the very strong difference in behavior in the two directions of the reinforcement. This example shows the need for taking into account the characteristics of the mechanical behavior in the simulation of forming, contrary to the geometrical approaches of draping type.